Study Of Reproductive Health Knowledge Through “Early Age Sexual Education” - Mediawati, Mika (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2020)
Reproductive health is a well-being condition of physically, mentally, socially as whole in every thing that linked with system, functions and process of reproduction (cholil,1996). Knowledge about reproduvtive health is very important to give for youngster for preventing any risk of sexual disorder that away such as pregnancy outside of marriage, sexual harassment, and sexual transmited diseases. Productive knowledge will more effective if it been given since kindergaten. According to Head Master of Aisyiyah IV Kindergaten statement,“Here are never get any special lecture about early age sexual education. All the time, sexual education still remain taboo, so the lecture still few”. Community service consists of several activities, such as counseling, singing, accompaniment, monitoring and evaluation, activities divided into three phase, Pengabmas phase I, II and monitoring and evaluation. Result of Pre-Post test showing not only knowledge but also enthusiastic increasement from participant that raising hand for answer the question given. Subject and song that been given can be given continuously for educated student as a reminder and for newly student that haven’t get educated before